Effect of repetition duration-total and in different muscle actions-on the development of strength, power, and muscle hypertrophy: a systematic review - Moreno-Villanueva, A.; Pino-Ortega, J.; Rico-González, M. (Strength and Conditioning Journal, 2022)
The aim of this systematic review was (a) to identify the articles that have differentiated muscle action duration (MAD) in the eccentric (ECC) and concentric (CON) muscle action regimen during resistance training (RT) programs and (b) to analyze how MAD affects strength, power, and muscle hypertrophy adaptations. Twenty-four studies were included from 3 electronic databases. The results showed that the RT protocols with medium ECC MAD and fast CON MAD, specifically cadences 2-4/0/1/0, produced the highest improvement values for the development of maximum dynamic strength, both in trained (18-24%) and untrained subjects (10-14%). For the development of maximum power, a medium total repetition MAD of less than 4 seconds and slow total repetition MAD, less than 8 seconds, seems suitable for untrained and trained subjects, respectively, with the condition that CON MAD is explosive or fast (cadence 4-8/0/max-3/0). Finally, muscle hypertrophy could be improved with a total repetition MAD less than 8 seconds in both trained and untrained subjects. The optimal timing of each muscle action to maximize hypertrophic training results is still not entirely clear. In conclusion, the prescription of the MAD, total and phase specific, should be planned according to the adaptations desired in untrained and trained individuals.